(untitled) (Baghdad Science Journal, 2023)
Metal contents in vegetables are interesting because of issues related to food safety and ‎potential health risks. The availability of these metals in the human body ‎may perform many biochemical functions and some of them linked with various diseases at ‎high levels. The current study aimed to evaluate the concentration of various metals in ‎common local consumed vegetables using ICP-MS. The concentrations of metals in vegetables ‎of tarragon, Bay laurel, dill, Syrian mesquite, vine leaves, thymes, arugula, basil, common ‎purslane and parsley of this study were found to be in the range of, 76-778 for Al, 10-333 for B, 4-119 for ‎Ba, ‎2812‎-24645 for Ca, 0.1-0.32 for Co, 201-464 for Fe, 3661-46400 for K, 0.31–‎‎1.53 for Li, 860-14330 for Mg, 16.20-71.5 for Mn, 612-4725 for Na and 15.8-46 µg ‎g-1 for Zn. The results revealed that the concentration of Al, B except in Syrian mesquite, Ba, Ca, ‎Fe, K, Mg and Mn in all analysed vegetables is higher than the recommended value, Li is ‎well-within the safe limit, and Co, Na except in dill, arugula and common purslane, Zn are ‎lower than the recommended intake of these elements. From health point of view, the HQ values for Al, Fe ‎‎(for all vegetables) and Ba (in dill, vine leaves, thymes, arugula, basil, common ‎‎purslane and ‎parsley) were higher than one, indicating potential non-cancer health risk due to exposure to ‎these metals. Furthermore, the HI value for all vegetables was higher than one, indicating ‎potential non-cancer health risk due to long-term exposure to these metals.